EDUCAÇÃO PARA AS RELAÇÕES ÉTNICO RACIAIS COM O MOVIMENTO CRESPOS/CACHEADOS EM CAXIAS-MA - ABREU, Edilene Rocha de (2024)
Education for ethnic-racial relations is a way to contribute to an inclusive society, especially when related to the experiences of the students themselves and by encompassing actions that value self-esteem and empowerment. The aim of this research is to provide means of dialogue and learning with the black movement, focusing on black aesthetics and corporeality as symbols of resistance in a society that still maintains standards defined by the colonization process. In this way, teaching expands the focus of the school curriculum from a Eurocentric history to a history of Brazil that values its cultural diversity, in accordance with Law 10639 of 2003, which amends Law 9394/96 (Law of Guidelines and Bases of National Education) on the teaching of Afro-Brazilian history and culture. In this sense, we seek to strengthen the ties between the school and the black movement, exchanging experiences with the Crespos/Cacheados Movement in the city of Caxias – MA, which works with black youth. To demonstrate the applicability of this research, a booklet on ethnic-racial education will be produced as a suggested educational material for high school history teachers.